El sistema dunar de Valdevaqueros: evolución histórica y alternativas de gestión. Issue 2 (1st July 2016) - Bello-Millán, F.J.; Somoano, M.; Clavero, M.; Gómez-Pina, G.; Losada, M.A.
Abstract: Valdevaqueros dune, in the south of Spain, exhibits high migration rates associated with strong easterly winds in the Strait of Gibraltar. The system is located in an area of high human pressure and its dynamic has collided with land use causing a significant impact from scientific and technical points of view but also from a media and social perspective. This paper focuses on the historical evolution of the dune system since the beginning of the 20th century by studying the available cartographic and photographic material, analyzing the different phases, the mechanisms and natural agents governing the dune behaviour and the implications arising from the activities in the area. The intervention on the dune corridor started in the early 1940s and has conditioned the evolution of all the processes in the physiographic region. The current dune morphodynamics is explained by the sediment budget. The system receives sand from the submerged zone, which is transported by westerly wind waves. This material accumulates and widens the dry beach. The easterly winds erode the sediment in the dry beach and transports it to the dune. In the last fifty years, the dry beach (fetch) has grown, on average, over 150 m and the system stores enough sand to sustain these transport mechanisms for decades. From these results, we discuss different alternatives for the integrated management of the area.